Analisis Kepuasan Pasien Di Rumah Sakit Umum Daerah Piru - Yerry Soumokil; Muhammad Syafar; Andi Yusuf (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: patient satisfaction is an "outcome" of health services. About improving the quality of health services. Objective: to find out how satisfied patients are in the midst of the Covid19 outbreak being treated. Methods: This research uses quantitative research, with a cross-sectional study approach that aims to determine the relationship between the two variables, namely the independent variable of service quality and the dependent variable of patient satisfaction which is carried out simultaneously. Results: showed that reliability, assurance, physical evidence, empathy, and responsiveness resulted in a p-value = 0.000 this means that there is a relationship between all variables with patient satisfaction. Conclusion: that there is a relationship between reliability, assurance, physical evidence, empathy, and responsiveness with patient satisfaction. Improving the quality of service is very necessary for expertise according to their respective scientific fields for all health service providers